Pengaruh Masker Peel-off Ekstrak Jagung (Zea Mays Saccharata) dan Bunga Melati (Jasminum Sambac L.) terhadap Perawatan Kulit Wajah Berjerawat - Hana Fadilla; Mitra Lusiana (Student Scientific Creativity Journal, 2025)
Acne is a common skin condition caused by excessive oil production that clogs pores and leads to inflammation. Acne-prone skin care can be done using facial masks, one of which is the practical and effective peel-off mask. This study aims to analyze the effect of using a peel-off mask containing corn and jasmine flower extract on acne-prone skin care. The research method used is a quasi-experimental design with a nonequivalent control group design. The sample consisted of six female students from Universitas Negeri Padang aged 17-25 years with acne-prone skin, divided into control and experimental groups. The research variables include the number, shape, color, and volume of acne. Data analysis techniques include normality, homogeneity, and hypothesis testing. The results show that the experimental group using the peel-off mask with corn and jasmine flower extract experienced a significant reduction in acne count, improvement in acne shape, and a decrease in redness and acne volume. In contrast, the control group showed no significant changes. Hypothesis testing indicated significance values for color (0.006), shape (0.000), volume (0.000), and number (0.000) <0.05, proving the effectiveness of the mask in treating acne-prone skin. In conclusion, the peel-off mask containing corn and jasmine flower extract is effective in reducing acne and improving facial skin condition.